Representation as repression: A First Peoples context - Thomas, Roie (Public Journal of Semiotics, 2021)
Visual images of a marginalised minority group from southern Africa are analysed against a series of colonialist representations to demonstrate tangible evidence of the role of representation in both disenfranchisement and an increasing autonomy in the case of the San, who are The First Peoples of the Kalahari, commonly known outside Africa as ‘Bushmen’ and in the dominant language of Botswana as Basarwa. This particular group is represented by government and its corporate affiliates as primordial for tourist consumption, yet systemically denied their language, ethnicity and ancestral land. Analysis is supported by critical tourism literature, showing the attitudes, power dynamics and practices evident in the produced imagery. An overview of the theoretical enframing and methodology is followed by analysis of a range of visual representations of the San. Analysis herein is based on a blend of application of post-colonial theory and post-tourism critique, along with some concepts from semiotics. Most of these visual and linguistic materials have been produced by government and industry for tourist consumption, while others include my own photography and ostensibly impartial museum exhibits.